PENERAPAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA BAGI SISWA KELAS VIIH SMP NEGERI 1 PIYUNGAN - SHEIRLY ERINE KAEMBA (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2023)
This study aims to improve student learning outcomes by implementing PBL (Project Based Learning). This research is a class action research (PTK) which consists of two cycles. Each cycle includes the stages of planning, implementing, observing, and reflecting. The subjects of this study were students of class VII H at SMP Negeri 1 Piyungan with a total of 30 students consisting of 12 male students and 18 female students. The data analysis technique used is descriptive qualitative. Based on the results and discussion, it can be concluded that the application of the PBL (Problem Based Learning) model to social arithmetic material can improve student learning outcomes in class VII H of SMP Negeri 1 Piyungan. In cycle I, the average student learning outcomes is 78.50. A total of 23 students met the KKM (Minimum Completeness Criteria) with a percentage of 76.67%. Meanwhile, there were 7 students who did not fulfill the KKM with a percentage of 23.33%. average student learning outcomes to 78.50 with a percentage of 76.67% completeness. so it is necessary to proceed with the action in cycle II. In cycle II, the average score was 86.50, which increased when compared to the average score in cycle I. The scores achieved by students in this knowledge assessment were 4 students whose scores were below the KKM or 13.33% of students who had not completed. Completeness of the new class reached 86.67%. ABSTRAKPenelitian ini bertujuan untuk meningkatkan hasil belajar siswa dengan menerapkan PBL (Project Based Learning). Penelitian ini merupakan penelitian Tindakan kelas (PTK) yang mana terdiri dari dua siklus. Setiap siklus meliputi tahap perencanaan, pelaksanaan, observasi, dan refleksi. Subjek penelitian ini adalah siswa kelas VII H SMP Negeri 1 Piyungan dengan jumlah 30 siswa yang terdiri dari 12 siswa laki-laki dan 18 siswa perempuan. Teknik analisis data yang digunakan adalah deskriptif kualitatif. Berdasarkan hasil dan pembahasan dapat disimpulkan bahwa penerapan model PBL (Problem Based Learning) pada materi aritmetika sosial dapat meningkatkan hasil belajar siswa kelas VII H SMP Negeri 1 Piyungan. Pada siklus I, rata-rata hasil belajar siswa 78,50. Sebanyak 23 siswa memenuhi KKM (Kriteria Ketuntasan Minimal) dengan persentase 76,67%. Sedangkan siswa yang tidak memenuhi KKM ada sebanyak 7 dengan persentase 23,33%. rata-rata hasil belajar siswa menjadi 78,50 dengan persentase ketuntasan 76,67%. sehingga perlu dilanjutkan dengan tindakan pada siklus II. Pada siklus II hasil nilai rata-rata adalah 86,50 mengalami peningkata jika dibandingkan dengan rata-rata nilai siklus I. Nilai yang dicapai siswa pada penilaian pengetahuan ini terdapat 4 siswa nilainya berada di bawah KKM atau 13,33% siswa yang belum tuntas. Ketuntasan kelas baru mencapai 86,67%.